Improving Dayaknese-Speaking Learners’ English Pronunciation - Ristati, Ristati; Suparwa, I Nyoman; Sudipa, I Nengah; Dhanawaty, Ni Made (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
The L1 influence causes difficulties for Dayaknese-speaking leaners (hereinafter referred to as learners) of English in producing English sounds. In English, pronunciation plays important role to understand the communication. The purposes of learning English pronunciation for learners are  (1) able to communicate in English clearly and intelligibly, (2) able to get the meaning of information conveyed in real life situations, (3) able to improve self-confidence while communicating oral English, and (4) able to monitor the use of English (able to listen, understand, and produce). The teaching of English subject in Indonesian schools includes four skills, namely listening, speaking, reading, and writing. While linguistic elements, such as vocabulary, grammar, pronunciation, and cultural patterns of discourse are the supporters of these four skills. This current research aimed to describe the implementation of behaviorism learning method and communicative approach as an attempt to improve English pronunciation for learners.  This current research was conducted by means of Research and Development (R & D) design, employing the stages as follows: analysis, design, development, implementation, and evaluation. Testing was done with experiment, which compares the effectiveness between the old (conventional) learning method and the new method (behaviorism learning method with a communicative approach). The indicators of the effectiveness of new method were the speed of the learners’ understanding, the learners’ creativity, and the learners’ learning outcomes.  Experiment was carried out by comparing with previous condition and after using a new learning method (before-after) or also called one group pretest-posttest. Based on statistical count, t count = -34.37 and t table = 1.67, the value of t count falls on Ha acceptance area (new learning method was more effective than conventional learning method) or Ha was accepted and Ho was rejected.